2016
DOI: 10.1109/tit.2016.2598350
|View full text |Cite
|
Sign up to set email alerts
|

Erasure/List Random Coding Error Exponents Are Not Universally Achievable

Abstract: Abstract-We study the problem of universal decoding for unknown discrete memoryless channels in the presence of erasure/list option at the decoder, in the random coding regime. Specifically, we harness a universal version of Forney's classical erasure/list decoder developed in earlier studies, which is based on the competitive minimax methodology, and guarantees universal achievability of a certain fraction of the optimum random coding error exponents. In this paper, we derive an exact singleletter expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In a breakthrough, Somekh-Baruch and Merhav [13] derived the exact random coding exponents for erasure decoding. Recently, Huleihel et al [14] showed that the random coding exponent for erasure decoding is not universally achievable and established a simple relation between the total and undetected error exponents. Weinberger and Merhav [15] analyzed a simplified decoder for erasure decoding.…”
Section: A Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In a breakthrough, Somekh-Baruch and Merhav [13] derived the exact random coding exponents for erasure decoding. Recently, Huleihel et al [14] showed that the random coding exponent for erasure decoding is not universally achievable and established a simple relation between the total and undetected error exponents. Weinberger and Merhav [15] analyzed a simplified decoder for erasure decoding.…”
Section: A Background and Related Workmentioning
confidence: 99%
“…where the notation γ(Q U|YQY ) is consistent due to the fact that the function γ(Q, R 2 ) (see (14)) only depends on the marginal distribution Q UY . Therefore, by using a similar argument as that for Ψ b1 above, we can remove the nonconvex constraint β(Q) ≥ 0 in Φ * a1 due to Φ * a2 .…”
Section: Proof Of Proposition 3: See Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it can be easily verified that this restriction is only needed for the analysis of E * l (R, T ), and so that analysis of E * e (R, T ) is valid for this list mode T < 0. Moreover, it can be shown that E * l (R, T ) = E * e (R, T )+T must be satisfied in general (which was shown in [6] only for the BSC), see [11,Lemma 1].…”
Section: Appendix Bmentioning
confidence: 99%
“…Over the years, research was aimed towards various extensions. For example, in [8,Chapter 10] [9], [10], [11] universal versions of erasure/list decoders, i.e., decoders that perform well even under channel uncertainty. In [12], the size of the list was gauged by its ρ-th moment, where ρ = 1 corresponds to the average list size, as in [1], and an achievable pair of error exponent and list size exponents was found.…”
Section: Introductionmentioning
confidence: 99%